Teologi og samfundsstudier - Holm, Bo Kristian (Dansk Teologisk Tidsskrift, 2012)
This review deals with three differing studies on the relation between religion and social formation. The focus of Frenkel and Lev’s Charity and Giving in Monotheistic Religions is on Islam, Judaism and Christianity in antique and medieval cultures, arguing that the monot heistic religions virtually agree in their understanding of charity and almsgiving. Berger, Davie and Fokas’ Religious America, secular Europe? offers a profound analysis of the relation between religion and moderni ty in contemporary society. I himlen således også på jorden? (On earth as in heaven?) by Hansen, Petersen og Petersen (eds.) examines the claim of a tight connection between Lutheranism and the Nordic welfare state. All three volumes deal with the social doctrine inherent in religion, but it is argued that, at least when it comes to the Lutheran tradition, theo logy cannot be seen as just having a social doctrine, since the doctrine of justifi cation can be seen as being a social doctrine in itself. This vital aspect should not be neglected while approaching the complex question of the role of religion in the formation of societies.